2018
DOI: 10.1016/j.dcn.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hubs in the human fetal brain network

Abstract: Advances in neuroimaging and network analyses have lead to discovery of highly connected regions, or hubs, in the connectional architecture of the human brain. Whether these hubs emerge in utero, has yet to be examined. The current study addresses this question and aims to determine the location of neural hubs in human fetuses. Fetal resting-state fMRI data (N = 105) was used to construct connectivity matrices for 197 discrete brain regions. We discovered that within the connectional functional organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 64 publications
4
53
0
1
Order By: Relevance
“…At first, we identified both connector hubs, which are thought to play an important role in integrating information from one module to other modules in the network (Rubinov & Sporns, 2010) and provincial hubs, hypothesized to serve as a relay station for information flow, exerting their influence mostly within their own submodule. Our data showed that the identified connector and provincial hubs largely overlap with regions previously described as hubs in the neonatal and fetal brain (de -Cruz et al, 2015;Gao et al, 2011;van den Heuvel et al, 2018) and also in the adult brain (Gong & He, 2015;He et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…At first, we identified both connector hubs, which are thought to play an important role in integrating information from one module to other modules in the network (Rubinov & Sporns, 2010) and provincial hubs, hypothesized to serve as a relay station for information flow, exerting their influence mostly within their own submodule. Our data showed that the identified connector and provincial hubs largely overlap with regions previously described as hubs in the neonatal and fetal brain (de -Cruz et al, 2015;Gao et al, 2011;van den Heuvel et al, 2018) and also in the adult brain (Gong & He, 2015;He et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…With regard to the problem of elevated head motion, errors introduced by movement cannot, at present, be fully corrected in fMRI time series. This fact necessitates application of stringent criteria for retaining only low-motion volumes to ensure data integrity, which is the approach taken by most studies to date [2,3,1,4,47]. We recommend two criteria for retaining low motion volumes: 1) framewise displacement less than 0.5mm, and 2) number of consecutive volumes reaching those criteria must be 10 or more.…”
Section: Realignment -5mmentioning
confidence: 99%
“…In recent years, this methodology has been applied to the human brain in utero, opening a window into a period of functional development that was otherwise inaccessible. Studying fetal fMRI has the potential to illuminate the nature and manner in which the brain's network architecture is initially assembled, affording powerful new insights into neurodevelopmental origins [1,2,3,4]. Despite this potential, progress has been slow due, in part, to the lack of image analysis tools tailored for fetal imaging data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations